Dermatomyositis Associated with Laryngeal Rhabdomyosarcoma: A Case Report - Gökçe Saygı UYSAL; Murat ÖZCAN; Sabri KÖSEOĞLU; Mehmet Ali ÇETİN and Hüseyin DERE (Archives of Rheumatology, 2013)
Dermatomyositis is a systemic autoimmune inflammatory disorder which is characterized by cutaneous manifestations and associated with various types of malignancies. Rhabdomyosarcoma is a rapidly growing, malignant mesenchymal neoplasm which arises from primitive muscle cells known as rhabdomyoblasts. The head and neck are the primary sites for rhabdomyosarcoma. To the best of our knowledge, concurrent dermatomyositis and rhabdomyosarcoma have not been reported before. In this article, we present a case with dermatomyositis and laryngeal rhabdomyosarcoma who was treated with surgery and chemoradiotherapy.